Kuliah Kerja Nyata Sebagai Wujud Pengabdian Mahasiswa Terhadap Masyarakat Di Desa Pulasan Tanjung Gadang Kabupaten Sijunjung - Pringgo Mardesia; Rona Khoirunnisa; Mella Alfianita Sari; Muhammad atthar (Culture education and technology research (Cetera), 2024)
The Real Work Lecture activity is an empowerment and community service program through the application of science, technology, and handling problems that occur in society in accordance with the Tri Dharma of Higher Education. The implementation of UNP KKN for the period June – July 2024 is an offline, placement-based KKN implementation. This activity aims to apply the knowledge gained and also find out the role of students in KKN activities as a form of service to the community during the 1 month period of service. The method of implementing service begins with problem identification, data collection and program planning, then program implementation. The results and conclusions show that KKN activities are a forum and proof that students are able to play a role and provide community service through the implementation of a series of work programs in Nagar Desai. The first is mutual cooperation at the mosque to welcome the new Islamic knowledge, the second is the implementation of a torchlight parade, stunting socialization with cadres. posyandu, holding the Pulasan Cup 2 tournament, outreach to 6 schools in Pulasan village regarding cleanliness, drugs, manners and bullying, coffee visits, gymnastics every Friday, and making a mini park from ecobricks.